Do Public Equity Markets Matter in Emerging Economies? Evidence from India - Gopalan, Radhakrishnan; Gormley, Todd A. (Review of Finance, 2013)
Abstract Do public equity markets serve an unique role that is not easily served by other forms of financing in emerging economies? We analyze this question using the collapse of India’s equity market in 1997, which provides an exogenous shock to firms’ ability to issue equity. We find that both public and private firms exhibit higher bankruptcy rates and lower growth after 1997. The decline in growth is greater among firms with more external finance needs and fewer tangible assets. Overall, the evidence suggests that public equity markets are an important, not easily replaced, source of finance in emerging economies.